Effect of Pd Precursor Salts on the Chemical State, Particle Size, and Performance of Activated Carbon-Supported Pd Catalysts for the Selective Hydrogenation of Palm Biodiesel - Parncheewa Udomsap; Apiluck Eiad-Ua; Shih-Yuan Chen; Takehisa Mochizuki; Nuwong Chollacoop; Yuji Yoshimura; Masayasu Nishi; Hiroyuki Tateno; Hideyuki Takagi (My University, 2021)
To improve the oxidative stability of biodiesel fuel (BDF), the polyunsaturated fatty acid methyl esters (poly-FAME) presented in commercial palm oil-derived biodiesel fuel (palm-BDF) were selectively hydrogenated to monounsaturated fatty acid methyl esters (mono-FAME) under a mild condition (80 °C, 0.5 MPa) using activated carbon (AC)-supported Pd catalysts with a Pd loading of 1 wt.%. The partially hydrotreated palm-BDF (denoted as H-FAME) which has low poly-FAME components is a new type of BDF with enhanced quality for use in high blends. In this study, we reported that the chemical states and particle sizes of Pd in the prepared Pd/AC catalysts were significantly influenced by the Pd precursors, Pd(NO3)2 and Pd(NH3)4Cl2, and thus varied their hydrogenation activity and product selectivity. The 1%Pd/AC (nit) catalyst, prepared using Pd(NO3)2, presented high performance for selective hydrogenation of poly-FAME into mono-FAME with high oxidation stability, owning to its large Pd particles (8.4 nm). Conversely, the 1%Pd/AC (amc) catalyst, prepared using Pd(NH3)4Cl2, contained small Pd particles (2.7 nm) with a little Cl residues, which could be completely removed by washing with an aqueous solution of 0.1 M NH4OH. The small Pd particles gave increased selectivity toward unwanted-FAME components, particularly the saturated fatty acid methyl esters during the hydrogenation of poly-FAME. This selectivity is unprofitable for improving the biodiesel quality.
Keywords: Carbon fibers; Biodiesel Production and Applications